Geopolymer lightweight bricks manufactured from fly ash and foaming agent - Wan Ibrahim, Wan Mastura; Hussin, Kamarudin; Abdullah, Mohd Mustafa Al Bakri; Abdul Kadir, Aeslina (American Institute of Physics, 2017)
This paper deals with the development of lightweight geopolymer bricks by using foaming agent and fly ash. The mix parameters analysed through a laboratory experiment with fix ratio of sodium silicate/sodium hydroxide solution mass ratio 2.5, fly ash/alkaline activator solution mass ratio 2.0, foaming agent/paste mass ratio 1:2 and molarity of sodium hydroxide solution used was 12M. Different curing temperature (Room Temperature, 60, 80) and foaming agent/water mass ratio (1:10 and 1:20) were studied. Compressive strength, density analysis, and water absorption has been investigated. The results show that the foamed geopolymer bricks with a lower foam/water mass ratio (1:10)and high curing temperature (80°C) leading to a better properties. Mixtures with a low density of around 1420 kg/m3 and a compressive strength of around 10 MPa were achieved.